Contact zones. Constructing identity in the Polish-Czech-German border region = Strefy kontaktowe. Konstruowanie tożsamości w polsko-czesko-niemieckim regionie przygranicznym - Spieker, Ira; Kleinmann, Sarah; Bretschneider, Uta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article results from a research project recently started at the Institute of Saxon History and Cultural Anthropology (Dresden) which aims to analyse "contact zones" in the Polish-Czech-German Border Region. It gives an insight into the work programme, discusses the methodological approach and presents some interim results. The time frame for the cultural-anthropological research project is set with reference to historical developments in these borderlands since World War II.
Keywords: rejony/obszary kontaktowe; pogranicze polsko-czesko-niemieckie; II (druga) wojna światowa; antropologia kulturowa; contact zones; remembrance; Polish-Czech-German border region; world war II; cultural anthropology